2014
DOI: 10.3389/fpsyg.2014.00168
|View full text |Cite
|
Sign up to set email alerts
|

When all children comprehend: increasing the external validity of narrative comprehension development research

Abstract: Narratives, also called stories, can be found in conversations, children's play interactions, reading material, and television programs. From infancy to adulthood, narrative comprehension processes interpret events and inform our understanding of physical and social environments. These processes have been extensively studied to ascertain the multifaceted nature of narrative comprehension. From this research we know that three overlapping processes (i.e., knowledge integration, goal structure understanding, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 166 publications
(525 reference statements)
1
22
0
3
Order By: Relevance
“…Yet, referential continuity was hard to construe even in pairs of "before-after" frames for Bantu (Zulu and Tsonga) workers in South Africa (Winter, 1963). Several studies have found continuity interpreted less often for native Africans compared to their European counterparts, including for Bantu populations (Duncan, Gourlay, & Hudson, 1973), native South Africans (Liddell, 1996(Liddell, , 1997, with the Basotho people (Jenkins, 1978), and in Botswana (Byram & Garforth, 1980), with results modulated by age, acculturation, literacy, and exposure to graphics. Lower proficiency on the PAT was observed for young men from the Ganda tribe (Uganda), despite proficient verbal (English) and math skills (John McFie, 1961), and for illiterate compared to literate Sudanese participants, while 80% of participants "failed to respond adequately" to the PAT in a pilot study (Khaleefa & Ashria, 1995).…”
Section: Cross-cultural Visual Narrative Comprehensionmentioning
confidence: 99%
“…Yet, referential continuity was hard to construe even in pairs of "before-after" frames for Bantu (Zulu and Tsonga) workers in South Africa (Winter, 1963). Several studies have found continuity interpreted less often for native Africans compared to their European counterparts, including for Bantu populations (Duncan, Gourlay, & Hudson, 1973), native South Africans (Liddell, 1996(Liddell, , 1997, with the Basotho people (Jenkins, 1978), and in Botswana (Byram & Garforth, 1980), with results modulated by age, acculturation, literacy, and exposure to graphics. Lower proficiency on the PAT was observed for young men from the Ganda tribe (Uganda), despite proficient verbal (English) and math skills (John McFie, 1961), and for illiterate compared to literate Sudanese participants, while 80% of participants "failed to respond adequately" to the PAT in a pilot study (Khaleefa & Ashria, 1995).…”
Section: Cross-cultural Visual Narrative Comprehensionmentioning
confidence: 99%
“…In children, development of narrative comprehension processes reaches a critical period between 3 and 5 years of age. From age 6, these processes continue to be refined until age 9, when sensitivity to goal structures and inferences resemble adult comprehension (Burris & Brown, 2014).…”
Section: Narrative Macrostructure and Comprehensionmentioning
confidence: 99%
“…Thus, assessing the development of ToM may be confounded by the concurrent development of “visual narrative fluency,” which is not measured. This confound may be a challenge to numerous domains that use visual narratives, including temporal cognition (Ingber & Eden, ; Weist, ), narrative cognition (Burris & Brown, ), and sequential reasoning (Zampini et al, ).…”
Section: Introductionmentioning
confidence: 99%